PEMANFAATAN GULMA LAHAN GAMBUT SEBAGAI BAHAN BAKU BIO-BRIKET - Pranatasari Dyah Susanti; Reni Setyo Wahyuningtyas; Adnan Ardhana (Jurnal Penelitian Hasil Hutan, 2015)
Weeds are abundantly available, which grow on peat swamps, but unfortunately have not yet been widely utilized. Those weeds can be prospectively potential as raw material for bio-briquettes. In relevant, this research aimed to look into the qualities of bio-briquettes manufactured from 10 species of peat swamp weeds. Initially, each weed species was carbonized and then shaped into charcoal powder. The resulting weed-charcoal powder was then mixed with wood sawdust at 1:1 ratio (w/w), and agitated thoroughly to obtain homogenous stuff. Afterwards, the homogenous stuff was added with starch-derived binder (adhesive). Such adhesive was previously prepared by heating 5 g tapioca-starch flour in 75 ml of water. The starch-added stuff was then pressed into bio-briquette, and further put in the oven at 60°C for 24 hours, or just dried under the sunlight heat for 2 days. The parameters as examined on the dried bio-briquette comprised calorific value, moisture content, fixed-carbon content, ash content, and sulfur content. Results revealed that the weeds of purun tikus (Eleocharis orrostachys Steud.) species was regarded as the best for bio-briquette manufacture, as it excelled other species in the overall examined parameters, i.e. calorific value (4,647.9 cal/g), fixed carbon (25.63%), moisture content (5.48%), ash content (8.78%) and sulfur (0.55%).